Construction of multiple electromagnetic loss mechanism for enhanced electromagnetic absorption performance of fish scale-derived biomass absorber. (1st July 2020) - Zhou, Xinfeng; Jia, Zirui; Feng, Ailing; Kou, Jiahao; Cao, Haijie; Liu, Xuehua; Wu, Guanglei
Abstract: Biomass-derived porous carbon materials have attracted considerable attention as promising electromagnetic (EM) wave absorbers due to their lightweight characteristic, ultra large surface area as well as high dielectric loss. However, the dielectric loss alone is difficult to achieve high EM wave absorption performance. In this work, core-shell Co@Co3 O4 /porous carbon composites are designed and synthesized by a facile hydrothermal and subsequent pyrolysis process through using fish scale as carbon precursor, Co(NO3 )2 ·6H2 O as Co source, aiming to offer more loss mechanism and achieve high EM wave absorption performance. As expected, the as-prepared composite showed strong absorption (−89.3 dB at 2.4 mm) with broadened bandwidth (11.92–18 GHz at 2 mm). Such excellent absorption performance could be attributed to the reasonable design of composite. Special porous structure not only is beneficial to the impedance matching to allow EM wave to enter absorber as much as possible, but also could offer a conductive path for electronic, booming conductive loss. Besides, the designed unique core-shell structure provides Co-Co3 O4 interfaces along with Co3 O4 -C, C-void interfaces are propitious to enhance interface polarization loss. Moreover, Co@Co3 O4 nanoparticles could also supply the magnetic loss to composites to further absorb EM wave from another point. Although there are many previous works about Co@Co3 O4 have been reported, little works have been done on the composites of biomass porous carbon with core-shell Co@Co3 O4 with such excellent EM wave absorption performance. This work indicates that the as-obtained core-shell Co@Co3 O4 /C could be a candidate for dealing with the increasing EM wave pollution. Graphical abstract: The interface polarization derived from plenty of interfaces, conductive loss originated from porous carbon skeleton along with magnetic loss caused by Co3 O4 @Co nanoparticles work together to attenuate EM wave. Image 1 Highlights: The micromorphology of composites could be easily tuned by changing cobalt salt amounts. Multicomponent endows the multiple loss mechanism to attenuate electromagnetic (EM) wave. The optimal EM wave absorption could up to −89.3 dB and broad effective bandwidth is 6.08 GHz.